2021
DOI: 10.1017/s193029750000855x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as infodemic: The impact of political orientation and open-mindedness on the discernment of misinformation in WhatsApp

Abstract: Messaging applications are changing the communication landscape in emerging countries. While offering speed and affordability, these solutions have also opened the way for the spread of misinformation. Aiming to better understand the dynamics of COVID-19 as infodemic, we asked Brazilian participants (n=1007) to report the perceived accuracy of 20 messages (10 true and 10 false). Each message was randomly presented within five fictitious WhatsApp group chats of varying political orientation. Correlational analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The type of information sources that one holds to be authoritative can indicate one's propensity to fall for fake news. Bonafé-Pontes et al (2021) found for Brazilian participants that those who trusted the credibility of social media news tended to be worse at truth discrimination; and conversely, those who trust the WHO and traditional media (newspapers, radio and television) tended to be better at truth discrimination. However, Tsang (2021) did not find any association between types of sources and the perception that a piece of "news" is false.…”
Section: Resultsmentioning
confidence: 86%
“…The type of information sources that one holds to be authoritative can indicate one's propensity to fall for fake news. Bonafé-Pontes et al (2021) found for Brazilian participants that those who trusted the credibility of social media news tended to be worse at truth discrimination; and conversely, those who trust the WHO and traditional media (newspapers, radio and television) tended to be better at truth discrimination. However, Tsang (2021) did not find any association between types of sources and the perception that a piece of "news" is false.…”
Section: Resultsmentioning
confidence: 86%